Managing broiler production challenges at high altitude - Fariborz Khajali (Veterinary Medicine and Science, 2022)
Abstract This review covers the challenges of broiler chickens at high altitude, with the focus on growth performance and physiological response. The review also sheds light on nutritional and management interventions that help overcome the challenges raised at high altitude. Reduced concentration of atmospheric oxygen is by far the biggest challenge that remarkably affect growth performance and livability of broiler chickens reared in high altitude area. Broiler chickens have endured intensive genetic selection, which potentially predispose them to several metabolic disorders. Hypoxia is an overriding factor that may increase the incidence of metabolic disorders, mainly ascites syndrome at high altitude. Commercial broiler strains cannot fully achieve their genetic potential when raising at highland regions. Careful nutrition and management considerations are required to prevent metabolic disorders when raising broilers at high altitude. In ovo or in‐feed nutraceuticals such as l‐carnitine and guanidinoacetic acid as well as pharmaceuticals, texture of feed and the use of proper sources and levels of dietary energy and protein are important factors that need to be carefully considered for rearing broiler chickens at high altitude. Management strategies such as lighting programs have been shown to be effective to circumvent ascites prevalence. Special breeding programs may also be considered to develop strains with resistance to ascites.